Моделювання складових національної еколого-економічної політики в рамках виконання Паризької угоди - Онищенко, А.М. (Економіко-математичне моделювання соціально-економічних систем, 2016)
On the ground of the optimizing control theory is suggested a two-sector ecology-economy model of the producer by emission of hotair gases limit. The authors discuss the necessity of the additional quota according to Paris Agreement. Economy-mathematical analyses allowed to construct the optimal trajectories and specifically turnpike trajectory.